2017
DOI: 10.1002/pbc.26730
|View full text |Cite
|
Sign up to set email alerts
|

Folate deficiency in north Indian children undergoing maintenance chemotherapy for acute lymphoblastic leukemia—Implications and outcome

Abstract: Background: Treatment-related toxicity and mortality are not uncommon during maintenance chemotherapy for childhood acute lymphoblastic leukemia (ALL), especially in the low-and middle-income countries (LMIC). Undernutrition and micronutrient deficiencies are commonly seen in children from LMICs undergoing treatment for ALL. The present study examines the prevalence and clinical implications of folate deficiency in north Indian children with ALL during the maintenance phase of treatment in view of prolonged an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Malnutrition in children with cancer, whether it be by overnutrition or undernutrition, has been linked to poor outcomes, greater rates of treatment discontinuation, hospital stays, treatment-related toxicity, infectious complications and mortality [ 7 ]. Hypotheses have been developed that suggest malnutrition impairs the ability of the immune response against infections due to cytokine hormone function alterations [ 8 ] and micronutrient deficiencies [ 9 , 10 ]. It also impairs the effectiveness of cancer treatments because of pharmacokinetic and pharmacodynamic changes that are explained by an altered metabolic state [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition in children with cancer, whether it be by overnutrition or undernutrition, has been linked to poor outcomes, greater rates of treatment discontinuation, hospital stays, treatment-related toxicity, infectious complications and mortality [ 7 ]. Hypotheses have been developed that suggest malnutrition impairs the ability of the immune response against infections due to cytokine hormone function alterations [ 8 ] and micronutrient deficiencies [ 9 , 10 ]. It also impairs the effectiveness of cancer treatments because of pharmacokinetic and pharmacodynamic changes that are explained by an altered metabolic state [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Akut lenfoblastik lösemi tanılı çocuklarda da idame tedavisi sırasında metotreksat (MTX)'ın yan etkisi olarak folik asit eksikliği ortaya çıkabilir. 4 Bu olgu sunumunda, ALL tanısıyla idame kemoterapisi aldığı sırada halsizlik ve burun kanaması nedeniyle kliniğimize başvuran ve pansitopeni tespit edilen bir hastamızın etyolojisinde folik asit eksikliği saptadığımızı belirterek konunun önemini vurgulamayı amaçladık. ateşi ve splenomegalisi olmaması, trigliserid ve fibrinojen seviyelerinin normal olması ve kemik iliği incelemesinde blast ve belirgin hemofagositoz saptanmaması üzerine relaps ALL ve HLH tanıları ekarte edildi.…”
Section: Introductionunclassified
“…9 Diğer yandan, idame tedavisi alan ve folik asit eksikliği olan ALL tanılı çocuklarda nötropeni ve trombositopeni gibi tedaviye bağlı komplikasyonların yaygın olup bazı çocuklarda kemoterapi dozunun azaltılmasını gerektirdiğini belirten çalışmalar da bulunmaktadır. 4 Kennedy ve arkadaşları da folik asit desteği ve MTX tedavisi arasındaki bağlantıyı araştırmışlar ve folik asit tedavisinin idame tedavisi alan ALL'li çocuklarda herhangi bir olumsuzluğa yol açmadığını belirtmişlerdir. 10 Akut lenfoblastik lösemili çocuklarda idame tedavisi sırasında folik asit eksikliği gelişebileceği akılda tutulmalı ve açıklanamayan pansitopeni varlığında serum kobalamin ve folik asit düzeyi kontrol edilmelidir.…”
Section: Introductionunclassified
“…Folate intake has also been associated with acute lymphocytic leukemia (ALL) risk and treatment outcome. Folic acid deficiency was associated with complications and adverse outcomes in children in India with ALL during maintenance chemotherapy 65 . In vitro studies have shown that human lymphocytes cultured in low FA concentrations have increased DNA instability, strand breakage, and uracil misincorporation 66 .…”
Section: Fa Deficiency and Neural Tube Defectsmentioning
confidence: 99%
“…Finally, folic acid deficiency was associated with complications and adverse outcomes in children in India with ALL during maintenance chemotherapy 65 . SNP 80G>A in the RFC1 gene, the reduced folate carrier, is associated with low plasma folate and high homocysteine concentrations in healthy persons 163 .…”
Section: Introductionmentioning
confidence: 99%